The Strong Influence of Nepotism on Corruption On The Buying of Positions In The Reason of Government - Gusman, Delfina (Journal of Law, Politic and Humanities, 2024)
Corruption has even become a bad habitdamage cornerstones of life in society and pollute the integrity of the nation. The widespread abuse of authority by state parties or officials in government agencies has become a culture aimed at increasing their wealth and even seeking promotion through nepotism. Nepotism is the tendency to prioritize (benefit) one's own relatives, especially in positions and ranks within the government. Nepotism in practice encourages people to do something or not do something as a shortcut to realizing personal benefits in the future through closeness to people who have positions in the agency. The strong influence of nepotism on the buying and selling of positions in the government domain has real detrimental impacts (actual loss). This research is legal research (doctrinal research) with a conceptual approach (conceptual approach), the legal approach (statues approach). The results of this research explain that the practice of nepotism which is part of criminal acts of corruption is very dangerous for the existence of the state, one of which is the integrity of the nation. Cases of nepotism that result in buying and selling positions often occur in government agencies due to greed and weak development supervision and the impact of state losses can be said to be real (actuall loss).